Dental stem cells culturing for the future - Abdullah, Muhammad Fawwad; Mokhtar@Makhtar, Khairani Idah; Thirumulu Ponnuraj, Kannan (Penerbit Universiti Sains Malaysia, 2016)
The importance of stem cells for various treatment purposes came to be realized after the advent of its prolific research. Stem cells are being popularly harvested from many sources such as embryo and bone marrow. However, harvesting and reaping the beneficial effects of stem cells from dental pulp is still cradling in its infancy. Indeed, there is a dearth of information on the detailed procedure of harvesting the stem cells from the dental pulp. This book is a compendium which highlights on the procedures of harvesting the stem cells from dental pulp and its characterization, with the aim to trigger the interests of the readers who are keen to venture further in this field.